Systemic Metaphors and Integrative Biology - Paton, Ray (Theoria et Historia Scientiarum, 2007)
The purpose of this paper is to provide a conceptual framework for examining and integrating systemic thinking in biology through the analysis of a number of systemic metaphors. After a brief examination of the roles that systemic metaphors can play in model development, a general framework is presented for integrating a range of key constructs such as hierarchy and organisation as well as the scope for use of the ecosystem metaphor. The idea of an ecology of biological information is used to encapsulate general thinking about networks, hierarchies and nestings at various scales and times and this leads on to the role played by the cognitive system metaphor. After a discussion of a number of occurrences of the cognitive metaphor a complementary systemic metaphor - verb-glue-text - is discussed. The paper concludes with a brief look at some of the conceptual constraints related to this metaphor. In order to make the paper integrative a broad range of biological examples are discussed from molecules to ecosystems.